Haematotrephus limnodromi n. sp. (Digenea: Cyclocoelidae) from the Long-billed dowitcher, Limnodromus scolopaceus (Scolopacidae) from the central flyway of North America - Dronen, Norman O.; Gardner, Scott L.; Jiménez, F. Agustín (Zootaxa, 2006)
During a study of the endohelminths of wading birds from the Texas Gulf coast, 5 specimens of an undescribed species of Haematotrephus (Cyclocoelidae) were studied and described. These specimens were collected by Dr. J. Teague Self, former professor, Department of Zoology, University of Oklahoma, Norman, Oklahoma from the air sacs of a long-billed dowitcher, Limnodromus scolopaceus, that was collected from the Cheyenne Bottoms, Roger Mills County, Oklahoma on August 3, 1963 and deposited in the Manter Laboratory of Parasitology. Haematotrephus limnodromi n. sp. can be distinguished from all the other species in the genus that lack an oral sucker (H. capellae, H. chengi, H. dollfusi, H. fasciatum, H. kossacki, H. lanceolatum, H. longisacculatum, H. nebularium, H. nigropunctatum, and H. phaneropsolus) by having intertesticular uterine loops. Corpopyrum brazilianum (originally described as Cyclocoelum brazilianum) is transferred as the second species in Selfcoelum, Corpopyrum dendrei is transferred to Neohaematotrephus, and Haematotrephus facioi is transferred to Wardianum. This is the first report of a species of Haematotrephus from a species of Limnodromus.